Pregnancy outcome after first trimester vaginal bleeding - Quraishi, Azhar Un Nisa; Khurshid, Rabia; Andrabi, Syed Aadil; Quraishi, Kamran Ahmad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: First trimester vaginal bleeding is one of the most common complications in pregnancy threatening its proper development and successful outcome. Methods: A case-control study was conducted from October 2016 to April 2018 in the department of obstetrics and gynecology SKIMS.200 cases with vaginal bleeding in first trimester were taken for study. Out of the cases, number of patients who had abortion, ectopic, molar pregnancy or continued their pregnancy beyond 20 weeks was noted. Those who continued their pregnancy were compared with 130 controls for complications developing later in pregnancy. Results: There was significantly higher incidence of PIH (15.4% of cases, 6.9% of controls, p value = 0.005) and abruption (7.7% and 1.5% among cases and controls respectively with p-value of 0.034) among cases than controls. Mean gestational age at delivery in cases was 35.6±3.63 weeks while in controls it was 38.5±1.94 weeks (p value <0.001). Mean birth-weight of the neonates in cases was 2.16±0.78 kgs while in controls was 3.05±0.53 kgs (p value <0.001). IUGR occurred in 9.2% of cases and 3.1% of controls (p value 0.039). There was significantly higher neonatal ICU admission rate in cases than controls (p value 0.019). Conclusions: Patients with first trimester vaginal bleeding are at increased risk for spontaneous loss and adverse pregnancy outcome.